Retrospective in silico analysis of routine laboratory data supports a specific association of Epstein-Barr virus and Multiple Sclerosis - Rodomonti, Mario; Pache, Florence; Otto, Carolin; Schindler, Patrick; Eberspächer, Bettina; Geran, Rohat; Puthenparampil, Marco; Gallo, Paolo; Wildemann, Brigitte; Jarius, Sven; Erdur, Hebun; Ruprecht, Klemens (European journal of neurology, 2025)
Background We conducted a retrospective in silico analysis of routine laboratory data (RISAROLDA) to study the association of Epstein-Barr virus (EBV) and multiple sclerosis (MS). Methods Patients with MS and 10 different inflammatory/neoplastic diseases were identified by ICD10 codes. Results of routine laboratory testing for antibodies to EBV, measles, mumps, rubella, herpes simplex virus, varicella zoster virus and cytomegalovirus were extracted using a digital tool. Results Among 10,669 patients with MS and 42,222 controls, EBV serologies were available from 492 (4.6%) patients with MS and 1918 (4.5%) controls. While all but three patients with an ICD10 diagnosis of MS were EBV seropositive, closer inspection of the three EBV seronegative patients revealed they were misdiagnosed with MS, resulting in a 100% EBV seroprevalence in the remaining 489 patients with MS. In contrast, EBV seroprevalences were lower in all other diseases (78.6%-97.8%). Serum antibodies to the Epstein-Barr nuclear antigen-1, but not to the viral capsid antigen, were higher in patients with MS than in all other diseases. In patients with MS, seroprevalences of all other common viruses were lower than those of EBV, but the frequency of intrathecal production of antibodies to EBV was lower than that of other common viruses. Conclusions These findings suggest that the association of EBV and MS is specific for MS as compared to various other inflammatory/neoplastic diseases and that a negative EBV serology might be a marker for the absence of MS. RISAROLDA is a powerful approach for the screening of real-world laboratory data.
Zuerst online veröffentlicht: 12. November 2025
Gesehen am 12.02.2026